Assessing Testing Strategies and Duration of Quarantine in Contact Tracing for SARS-CoV-2: A Retrospective Study of San Francisco’s COVID-19 Contact Tracing Program, June–August 2020 - Reid, M J A (Open Forum Infect Dis, 2021)
We sought to assess the proportion of elicited close contacts diagnosed with coronavirus disease 2019 at the start of and before exiting quarantine in San Francisco. From June 8 to August 31, 6946 contacts were identified: 3008 (46.3%) were tested, 940 (13.5%) tested positive, and 90% tested positive in the first 9 days of quarantine.